2020
DOI: 10.31234/osf.io/536w7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Religious People View Both Science and Religion as Less Epistemically Valuable Than Non-Religious People View Science

Abstract: Religion and science are two major sources of knowledge. Some accounts suggest that religious belief inhibits people from trusting scientific information, and encourages conflict between religion and science. We draw from theories of human motivation to challenge this claim, instead suggesting that religious people perceive less conflict between science and religion than non-religious people, that religious—but not non-religious—people use both science and religion when they explain phenomena, and that religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Further, as mentioned before, other research has shown that religious individuals are more likely to see compatibility between science and religion M. S. Evans, 2012;Falade & Bauer, 2018;Jackson et al, 2020a;Mackey et al, 2023;Vaidyanathan et al, 2016). Non-religious individuals, by contrast, are more likely to hold a "conflict" view Funk & Alper, 2015;Marin & Lindeman, 2021), and they tend to underestimate religious individuals' openness to science (Jackson et al, 2020;Study 6).…”
Section: Conflict Viewsmentioning
confidence: 83%
See 1 more Smart Citation
“…Further, as mentioned before, other research has shown that religious individuals are more likely to see compatibility between science and religion M. S. Evans, 2012;Falade & Bauer, 2018;Jackson et al, 2020a;Mackey et al, 2023;Vaidyanathan et al, 2016). Non-religious individuals, by contrast, are more likely to hold a "conflict" view Funk & Alper, 2015;Marin & Lindeman, 2021), and they tend to underestimate religious individuals' openness to science (Jackson et al, 2020;Study 6).…”
Section: Conflict Viewsmentioning
confidence: 83%
“…Scholars have attempted to test whether religious beliefs (or a lack thereof) are responsible for people's tendency to subscribe to the "conflict" view. This notion is based on the finding that, on the one hand, nonreligious individuals are more inclined to regard science as the only effective means of achieving instrumental goals, contributing to their stronger endorsement of the "conflict" view, and that, on the other hand, religious individuals are more likely to perceive science and religion as equally instrumental (i.e., the instrumentality hypothesis, Jackson et al, 2020aJackson et al, , 2020b. A line of evidence, indeed, substantiates this notion by revealing that religious individuals tend to view scientific and religious explanations as equally instrumental, while nonreligious individuals rely solely on scientific explanations (Jackson et al, MENTAL CONCEPTUALIZATION OF SCIENCE AND RELIGION 2020a, Study 3; see also Funk & Alper, 2015).…”
Section: Religionmentioning
confidence: 99%
“…Furthermore, as mentioned previously, other research has shown that religious individuals are more likely to see compatibility between science and religion Evans, 2012;Falade & Bauer, 2018;Jackson et al, 2020a;Mackey et al, 2023;Vaidyanathan et al, 2016). In contrast, nonreligious individuals are more likely to hold a "conflict" view Funk & Alper, 2015;Marin & Lindeman, 2021), and they tend to underestimate religious individuals' openness to science (Jackson et al, 2020a;Study 6). Furthermore, recent studies suggest that religious exclusivism (rather than religiosity alone; see Lee, 2022) and antireligious attitudes (Francis et al, 2019b) have independently contributed to a stronger endorsement of the "conflict" view.…”
Section: Conflict Viewsmentioning
confidence: 84%
“…However, not all studies have found a consistent correlation between religiosity and negative attitudes toward science, as evidenced by a cross-cultural study (McPhetres et al, 2021). Furthermore, as mentioned previously, other research has shown that religious individuals are more likely to see compatibility between science and religion Evans, 2012;Falade & Bauer, 2018;Jackson et al, 2020a;Mackey et al, 2023;Vaidyanathan et al, 2016). In contrast, nonreligious individuals are more likely to hold a "conflict" view Funk & Alper, 2015;Marin & Lindeman, 2021), and they tend to underestimate religious individuals' openness to science (Jackson et al, 2020a;Study 6).…”
Section: Conflict Viewsmentioning
confidence: 89%
See 1 more Smart Citation